Paragony - Azizan, Irdina Firzana; Ishak, Eliza Shafiqa; Abd Jalil, Naja Najwa; Razak, Siti Safuah; Jamil, Nur Hanisah; Mohd Yusoff, Muhammad Amirul Hakimi (2015)
PARAGONY is a manufacturing business that produces and sells portable food containers made from non-toxic, high-quality raw materials. Located at 80/1, Jalan Pendidikan 4, Taman Universiti, 81300 Skudai, Johor, the company's core mission is to ease modern life by introducing an innovative product. To compete effectively, PARAGONY highlights a key feature that distinguishes its container from others on the market: it is collapsible. This design makes the product exceptionally portable, easy to carry anywhere, and capable of fitting even into a pocket. The company is confident that this unique feature will capture consumer attention, allowing PARAGONY to gain market share and achieve the same level of success as its benchmark competitor, Tupperware. The business recognizes the strong potential for success, provided it is managed efficiently, as the product directly addresses the modern consumer's demand for convenience. The company's tagline is "PARAGON, Think space".